1964
DOI: 10.1002/hlca.19640470213
|View full text |Cite
|
Sign up to set email alerts
|

Verdoppelungserscheinungen beim Ringschluss Von Peptiden. V. Relative Bedeutung der sterischen Hinderung und der Assoziation über Wasserstoff‐Brücken bei Tripeptiden. Spektroskopische Versuche zur Konformationsbestimmung. 12. Mitteilung über homodet cyclische Polypeptide

Abstract: Volumen 47, Fasciculus 2 (1964) -No. 54 44 1 54. Verdoppelungserscheinungen beim Ringschluss von Peptiden V. Relative Bedeutung der sterischen Hinderung und der Assoziation iiber Wasserstoff-Briicken bei Tripeptiden. Spektroskopische Versuche zur Konformationsbestimmungl). 12. Mitteilung iiber homodet cyclische Polypeptide [l] 2, von R. Schwyzer3), J. P. Carribn, B. Gorup, H. Nolting und Aung Tun-Kyi (21. XII. 63) 1. Problemstellung

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…It was shown that to maintain high membranolytic activity, it is important to (1) preserve the β-sheet-like structure within the cyclic molecule, at least when it is bound to cell membranes, (2) maintain the net positive charge and amphipathic “sidedness” of the GS molecule, and (3) make sure that the molecule has a sufficiently high overall hydrophobicity. Structural considerations led to the conclusion that cyclic peptides would form stable β-hairpins only if they contain an even but not an odd number of amino acid residues . Residues with high β-conformational propensities (Val, Ile, Thr, Phe, Tyr, and Trp) should be preferably placed within the β-strands .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that to maintain high membranolytic activity, it is important to (1) preserve the β-sheet-like structure within the cyclic molecule, at least when it is bound to cell membranes, (2) maintain the net positive charge and amphipathic “sidedness” of the GS molecule, and (3) make sure that the molecule has a sufficiently high overall hydrophobicity. Structural considerations led to the conclusion that cyclic peptides would form stable β-hairpins only if they contain an even but not an odd number of amino acid residues . Residues with high β-conformational propensities (Val, Ile, Thr, Phe, Tyr, and Trp) should be preferably placed within the β-strands .…”
Section: Resultsmentioning
confidence: 99%
“…Structural considerations led to the conclusion that cyclic peptides would form stable β-hairpins only if they contain an even but not an odd number of amino acid residues. 68 Residues with high β-conformational propensities (Val, Ile, Thr, Phe, Tyr, and Trp) should be preferably placed within the β-strands. 69 It also turned out that delicate changes in the composition, leading to a modulation of amphipathicity and overall hydrophobicity of the parent molecule, generated more selective antibacterial GS analogues.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…The cyclizations of a linear tripeptide and a linear pentapeptide give a cyclic hexapeptide and a cyclic decapeptide, respectively, as a major product. Schwyzer (25) explained the cyclo-dimerization in terms of an intermolecutar association due to hydrogen bonding of two linear peptide chains forming an antiparallel ~-structure prior to the reaction. But later, other factors than the intermolecular association inducing the dimerization reaction during the cyclization reaction of small peptides were investigated (25).…”
Section: Synthesis Of Cyclic Peptidesmentioning
confidence: 99%
“…Schwyzer (25) explained the cyclo-dimerization in terms of an intermolecutar association due to hydrogen bonding of two linear peptide chains forming an antiparallel ~-structure prior to the reaction. But later, other factors than the intermolecular association inducing the dimerization reaction during the cyclization reaction of small peptides were investigated (25). Steric hindrance seemed to play a prominent role in the cyclization of tripeptides to cyclic hexapeptides.…”
Section: Synthesis Of Cyclic Peptidesmentioning
confidence: 99%
See 1 more Smart Citation